ACID ASPIRATION PROPHYLAXIS DURING ANAESTHESIA FOR CAESAREAN SECTION: A SURVEY AMONG ANAESTHETISTS AT HYDERABAD - Shaikh, Jan Muhammad; Sabbar, Saleem; Aziz, Nasir; Shaikh, Najma Bano; Akhund, Tauseefullah (Journal of Ayub Medical College Abbottabad, 2009)
Background: Pulmonary aspiration of gastric contents leading to acid aspiration syndrome (AAS) is a well recognized risk factor during general anaesthesia (GA) for Caesarean section (CS). The cross sectional observational study was conducted during July 2008 to October 2008 at Department of Anaesthesiology and Intensive Care, Liaquat University of Medical & Health Sciences Jamshoro, Sindh, Pakistan. The objective was to assess anaesthetic practice patterns and measures to prevent aspiration of acid gastric contents in full term pregnant women undergoing anaesthesia for Caesarean section. Methods: A structured questionnaire regarding practice of anaesthesia for Caesarean section was distributed among anaesthetists working and practicing at Hyderabad. Results from the completed questionnaires were transferred to a Microsoft Excel spreadsheet and the responses represented as percentages. Results: General anaesthesia was preferred by 75.4% anaesthetists for caesarean section, 83.6% anaesthetists used rapid sequence induction with cricoid pressure during general anaesthesia, 29.5% respondents restricted clear fluids for 2-3 hours. Antacids were used by 90% of the anaesthetists, while about 50% anaesthetists performed extubation when patients were fully awake. Conclusion: Recommended practice patterns and measures to prevent aspiration of acid gastric contents during anaesthesia for caesarean section are not observed by most of the anaesthetists working at Hyderabad. Keywords: Caesarean Section, Anaesthesia, Acid Aspiration Prophylaxis